SEMIOTYCZNE ASPEKTY DYSKUSJI O PAŃSTWIE PRAWNYM - Wieczorkiewicz-Kita, Joanna; Kanarek, Beata (Wydział Prawa i Administracji UAM, 1998)
The article is an attempt to determine semiotic status of the statements on a State of law and, in the same time, an attempt to fix up the significance of the pronouncement “a State of law”. This term was only recently admitted to function in Polish juridical language; it was introduced in 1989, in December, by the new Constitution of Poland. The Authors analyse the meaning of this term in different linguistic and logical aspects, express their opinions on conceptions of other authors and cite a very rich literature of the subject.
SEMI OTIC ASPECTS OF THE DISCUSSION ON A STATE OF LAW